Lean Manufacturing Implementation in Indonesian Coffee Processor - Sony Suwasono; Shinta Syafrina Endah Hapsari; Ida Bagus Suryaningrat; Djoko Soemarno (International Journal on Food, Agriculture and Natural Resources, 2022)
The rapid competition between business and sustainability policy has encouraged the coffee industry in Indonesia to make their business more environmentally friendly. However, this initiative has yet to be fully underway. Several inefficiencies still prevail in Arabica coffee production sites, such as product defects in inventory, the inefficiency of production machine performance, and dependence on manpower that can increase the production and inventory costs. Therefore, the Arabica coffee agroindustry needs to improve its performance by addressing these issues in production activity using the lean manufacturing approach. Several tools proven influential to reduce waste in the agroindustry are Value Stream Mapping (VSM) and VALSAT. VSM could document the entire mapping of material and information management, but cannot classify the time required to complete the whole process. VALSAT has several derivative tools, but polyacrylamide (PAM) and Supply Chain Response Matrix (SCRM) are mostly used in agroindustry to classify value-added time of processes and illustrate the supply chain cumulative inventory of a company. The result of this study shows that the Indonesian Arabica coffee industry could reduce its cycle time by 57%, lead time by 63%, and changeover time by 50%. In addition, the recommendations result in the involvement of only 2 people during the drying process and eliminate the non-value-added time, while improving the overall production efficiency and capacity.